Acetylation-modulated communication between the H3 N-terminal tail domain and the intrinsically disordered H1 C-terminal domain. Issue 20 (30th October 2020) - Hao, Fanfan; Murphy, Kevin J; Kujirai, Tomoya; Kamo, Naoki; Kato, Junko; Koyama, Masako; Okamato, Akimitsu; Hayashi, Gosuke; Kurumizaka, Hitoshi; Hayes, Jeffrey J
Abstract: Linker histones (H1s) are key structural components of the chromatin of higher eukaryotes. However, the mechanisms by which the intrinsically disordered linker histone carboxy-terminal domain (H1 CTD) influences chromatin structure and gene regulation remain unclear. We previously demonstrated that the CTD of H1.0 undergoes a significant condensation (reduction of end-to-end distance) upon binding to nucleosomes, consistent with a transition to an ordered structure or ensemble of structures. Here, we show that deletion of the H3 N-terminal tail or the installation of acetylation mimics or bona fide acetylation within H3 N-terminal tail alters the condensation of the nucleosome-bound H1 CTD. Additionally, we present evidence that the H3 N-tail influences H1 CTD condensation through direct protein-protein interaction, rather than alterations in linker DNA trajectory. These results support an emerging hypothesis wherein the H1 CTD serves as a nexus for signaling in the nucleosome.